Planning of Casing Design in AOV-1 Well Drilling, ANTARIS Field KSO Pertamina EP – Banyubang Blora Energi (BBE) - Bambang Ariyanto; Nur Suhascaryo (PETRO: Jurnal Ilmiah Teknik Perminyakan, 2021)
The AOV-1 well is a development well that is planned to be drilled in the “ANTARIS” Field. Based on the data obtained from the nearest well of “AOV-1” well, a casing design will be carried out, therefore it is necessary to select casing specifications. So that it can meet the requirements technically and economically.               Casing design planning is the preparation of file collected from drilling prognosis, and daily drilling report so that it can be used for calculation of pressure parameters, knowing stratigraphy, lithology, subsurface data, availability of casing stock in warehouse, and planning technical calculations for casing design operations such as d-exponent calculation to determine pore pressure, pressure calculation (formation pressure, overburden pressure, fracture pressure), calculation of the load received by casing (burst load, burst load design, collapse design), determination of casing setting depth, casing grade selection for casing design, calculation of biaxial stress correction of tension and compression stress, calculation of safety factor, and finally, calculation of economics from planning casing design.               7 ” casing program grade K-55, 20 PPF, BTC at a depth of 0 - 1968.5 ft TVD with safety factor Ni = 3.83 each; Nc = 2.19; Nj = 13.54, only 1 section is performed. casing program 9/8 " Casing program  with grade K-55, 36 PPF, BTC at a depth of 0 - 820 ft. TVD with a safety factor of each Ni = 9.91; Nc = 4.83; Nj = 30.06, only 1 section is performed. 13 3/8 " casing program with grade K-55, 54.5 PPF, BTC at a depth of 0 - 250 ft. TVD with a safety factor of each Ni = 63.77; Nc = 22.99; Nj = 226.73, only done 1. The total cost for casing planning is $ 57,689 or around Rp. 816,876,240 of the budget provided, which is $ 65,000 or around Rp. 920,400,000.